Use of Cannabis sativa in the treatment of epilepsy - a literature review (Research, Society and Development, 2021)
Epilepsy is a chronic neurological disorder, where abnormal electrical discharges occur, causing seizures in those affected with this pathology. The medicinal power of Cannabis sativa has been known for several centuries, but in recent years there has been an increase in studies on the use of one of its compounds, cannabidiol, for the treatment of various diseases, such as Parkinson's, Alzheimer's, Sclerosis Multiple, anxiety, depression and especially in epilepsy. This work is a literature review with the purpose of gathering information and describing it in a clear and objective way, providing a broader view on the use of Cannabis sativa in the treatment of epilepsy. Data were collected through documents, books, articles, magazines and texts, material available in the databases. The conclusion is that cannabidiol has therapeutic capacity for the treatment of patients with epilepsy and convulsive crisis, but further studies are still needed to understand the compounds of Cannabis sativa, both for the treatment and its side effects in